Biomimetic smart brace using metamaterial structures - Tan, Phei Shien (Nanyang Technological University, 2021)
Ankle sprains are one of the most common injuries experienced by both athletes and non-athletes alike. This creates market opportunity for manufacturers to develop ankle brace for the ankle to prevent such injuries. However, current braces limit range of motion and are standardised for the customers. The ankle braces are unable to cater to all individuals as needed due to individually differing foot types and measurements, leading to discomfort after prolonged use. This project used metamaterial structures to vary the Young’s Modulus of the ankle brace according to customised needs. The metamaterial horseshoe structure was 3D printed and allowed for a functional range of motion at low strain and restraint the ankle using a strain-limiting behaviour at higher strain. The structure has quantifiable parameters which allow for ease of customised protection based on their individual measurements. A testing jig was also developed to test the mechanical properties of the printed jig against other ankle braces. The results of the proof-of-concept showed that the prototyped ankle brace using the horseshoe structure allowed for a lower Young’s Modulus at a low strain and exhibited strain-limiting behaviour at desired strain levels, catering to individual needs. The ability of the structure to be 3D printed also enables ease of mass production.